Perbedaan Hasil Usaha Buah Melon Yang Menggunakan Naungan Dan Tidak Naungan - Wiyanto, Andi; Siti Sundari, Ristina; Setia Umbara, Dona (Universitas Gajah Putih, 2023)
Melon fruit is one of the horticultural plants that are widely consumed by the public, with a content of 54% and 49% daily nutritional adequacy levels in vitamins A and C, containing minerals, sodium, iron, potassium, magnesium, phosphorus and fruit flesh containing carotenoids for the body's immunity. Agricultural cultivation requires sophisticated technology to facilitate farming activities, one of which is the Tunas Harapan farmer group. One of the communities in Tasikmalaya city that cultivates melons with shade treatment and not shade. This study aims to find out how the results of melon farming using shade and not using shade differ. The results of this study show that the total amount of costs on shade is Rp.1.187.366 while non-shade is Rp.1.111.660 with a difference of Rp.75.706 in one planting period, total income on shade is Rp. 2.462.634 while non-shade is Rp.1.925.840 with a difference in total income of Rp.536.794 and the amount of production in shade is 146 kg while non-shade is 121.5 kg with a difference in total yield of 24.5/kg in one planting period. It can be known that there is a difference between melon farming using shade is higher than melon farming business that does not use shade, this shows that using shade is more profitable than not using shade. In the ratio of melon farming, it can be seen from the two treatments that melon farming using shade is relatively high with a value of 3,0 and does not use shade of 2,7.